Climate alterations, Lords of the land, and social life of Black frees and slaves in Piura: 1791-1823 - Espinoza Claudio, César (2020)
This research presents the social dynamics of the existing black population that inhabited inside and outside the city of San Miguel de Piura, in a context of the political crisis of the viceregal domination. We reviewed several judicial processes located in the Regional Archive of Piura, about the intensity of the rains and floods, the cycles of dry years, and their destructive impacts on the fields of cultivation and grazing, belonging to the Haciendas and farmland. We examine the social resistance of a population that survived on rivers banks from the coast and the highlands of Piura, turned into farmers or settlers, to produce grains and meats for the supply of Piura’s city. We analyze the conformation of Marronage and Palenques in the carob and sapote mountains surrounding the city and within large landowner’s estates. Finally, we detailed the complex social life of Black frees and slaves, who were facing drought and rain cycles, fires and sterilities, in Haciendas lands located between Olmos and Tambogrande, and also between Pabur and the city of San Miguel de Piura during 1791-1823.